PENGEMBANGAN KAPASITAS RUKUN TETANGGA/RUKUN WARGA SEBAGAI ORGANISASI ‘AKAR RUMPUT’ DALAM ERA DESENTRALISASI LUAS - Tri Widodo W. Utomo Betha Miranti Andalina (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2009)
In line with the current socio-economical dynamic, grass-root organizations become more and more important. The formation of grass-root organizations should be complemented by the process of building their capacity so that the grass-root organizations positively bring in horizontal and vertical impacts. Among other elements of village government apparatus, which holds important roles, are Neighborhood and Hamlet Associations. Their existence and functions as grass-root organizations represent one main component of community-centered local government. The associations constitute the front-liners in giving services to community due to their closeness to the community. Therefore, capacity development for these grass-root organizations becomes an immediate necessity that needs positive response. A concrete policy should be formulated to leverage their existence and and functions so that they can contribute to the socio-economicdevelopment. Although structurally they are not part of local government institutions, their roles are embedded with the main functions of local government